A hypothesis: CRISPR-Cas as a minimal cognitive system. (June 2019) - Yakura, Hidetaka
Concerning what signifies the minimal requirements for a process to be designated cognitive, various criteria have been proposed, but the problem has not been settled. The important thing to consider in establishing the criteria is which criterion has stronger explanatory power. Recent developments in immunology demonstrate that the immune system is omnipresent in the realm of living beings, including bacteria and archaea. Although the structural characteristics of immune systems are significantly different among species, the fundamental functional components, namely, recognition, information integration, reaction, and memory, are well conserved. Interestingly, these adaptive features are superimposed on those of the central nervous system. Given that adaptive cognitive ability is a prerequisite for the existence and the survival of living organisms, these results may be compatible with the idea that in bacteria without an apparent nervous system, the immune system performs neural-like functions. The presence of the clustered regularly interspaced palindromic repeats (CRISPR)-CRISPR associated protein (Cas) systems as a cognitive system in the earliest living organisms suggests that one of the fundamental functions is conserved throughout evolution. Furthermore, this interpretation can evade the critiques against the current biological paradigm that demand that cognitive mechanisms be preceded by organisms in the earlier stages of evolution, thus providing better and stronger explanatory power. I thus propose that genetic and biochemical machinery represented by the bacterial immune system serves as a minimal cognitive system.